A System-Theoretic Accident Model and Process with Human Factors Analysis and Classification System taxonomy. (December 2018) - Lower, Michał; Magott, Jan; Skorupski, Jacek
Highlights: STAMP error taxonomy has been extended by HFACS taxonomy. HFACS elements are incorporated into STAMP safety control structure. One thread of Überlingen aviation accident was analyzed by STAMP-HFACS method. Accident described as structure of: contexts, decisions and actions, process flaws of component properties. The results of thread analysis are represented in A-CAST software tool. Abstract: Formal methods are necessary for effective analysis of the causes of complex accidents. One of possibilities is the System-Theoretic Accident Model and Processes (STAMP) using a hierarchical safety control structure for finding control flaws leading to hazards. The aim of this paper is to enhance STAMP error taxonomy by Human Factors Analysis and Classification System (HFACS). The method proposed in this paper is STAMP-HFACS framework for accident analysis. This framework is STAMP structure-driven, i.e. levels of the HFACS structure are incorporated into components of the STAMP safety control structure. A result of the proposed procedure is the STAMP-HFACS diagram. To illustrate the applicability of the method one thread of the Überlingen midair accident was analyzed. The STAMP-HFACS methodology can express interactions between people, technical equipment, and the environment. It is not bound to an incident/accident events chain. It allows for an analysis of a safety-related occurrence focused on finding some adverse relationships between the components, especially at higher levels of the HFACS methodology. Proper recognition of these relationships, and especially their interpretation in system-theoretic terms related to specific components, can be of great importance for increasing the level of air traffic safety.